Long coding RNA CCAT2 enhances the proliferation and epithelial-mesenchymal transition of cervical carcinoma cells via the microRNA-493-5p/CREB1 axis. Issue 1 (1st January 2021) - Wang, Jing; Liu, Yan; Cai, Hongbing; Jiang, Hong; Li, Wei; Shi, Yuying
ABSTRACT: Cervical cancer (CC) is one of the most common malignancies among women. It has been demonstrated that long coding RNAs (lncRNAs) play a crucial role in CC. The purpose of this study was to investigate the role of the colon cancer associated transcript 2 (CCAT2) lncRNA in CC and elucidate its possible mechanisms of action. The expression of CCAT2, the miR-493-5p microRNA (miRNA), and mRNA was detected using qRT-PCR. Cell viability, proliferation, and migration and invasion were determined using the MTT, colony formation, and transwell assays, respectively. The interactions between miR-493-5p and CCAT2 or cAMP response element-binding protein 1 (CREB1) were verified using the luciferase and RNA pull-down assays. The effects of CCAT2 knockdown on in vivo tumor growth were determined using tumor xenografts and immunohistochemistry assays. The expression of CCAT2 was upregulated in CC cells and tissues. However, the knockdown of CCAT2 inhibited the proliferation and epithelial-mesenchymal transition (EMT) of CC cells in vitro and suppressed tumor growth in vivo . Mechanistically, CCAT2 functions as a competing endogenous RNA (ceRNA) to upregulate the expression of CREB1 by binding to miR-493-5p. The overexpression of CREB1 or downregulation of miR-493-5p antagonized the effect of CCAT2 knockdown on the proliferation and EMT of CC cells. The knockdown of CCAT2 suppressed the aggressiveness of CC via the miR-493-5p/CREB1 axis. Therefore, CCAT2 is likely to be a promising therapeutic target for CC.